WITH LOVE FOR THE SACRED LANGUAGE (American Journal of Interdisciplinary Research and Development, 2023)
Some people think that it is easy for non-native speakers of Arabic to learn, but in reality, any language learner faces some obstacles in the learning process, so it takes a long time to learn the language. These problems include everything related to phonetic, morphological, grammatical, semantic, and writing skills. There are also problems unrelated to linguistics, such as in social, cultural, psychological, cognitive, economic, and historical fields. Pronunciation problems are one of the first problems that a student may encounter in any language because, in the early stages of language learning, he learns the denominator of sounds. If a person learns from a young age, it is not difficult to pronounce letters, but adults who learn a second language often have difficulty pronouncing certain sounds, and this is because some letters do not exist in their native language.